2014
DOI: 10.2355/isijinternational.54.2369
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Hydrogen Embrittlement on Hot-sheared Surface during Die-quench Process

Abstract: This study investigated the resistance of hydrogen embrittlement on a hot-sheared and quenched surface of 22MnB5 steel sheets. The specimens were sheared at 750°C and 650°C after austenitization, and then quenched by water cooling. Additionally, these specimens were cathodically hydrogenized for 48 h to accelerate cracking by hydrogen embrittlement. This sequence resulted in a residual tensile stress of over 1 GPa on the hot-sheared surface and a diffusible hydrogen density of about 1.5 ppm. Despite these seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…He suggested that tempering above 200 o C is not recommended for MS-AHSS as this treatment leads to a significant loss in strength but without the expected improvement in ductility, toughness and bendability. Finally, Matsuno et al [53] observed that ductile phases like ferrite and bainite lessen the hydrogen sensitivity of hot-sheared quenched 22MnB5 steels.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…He suggested that tempering above 200 o C is not recommended for MS-AHSS as this treatment leads to a significant loss in strength but without the expected improvement in ductility, toughness and bendability. Finally, Matsuno et al [53] observed that ductile phases like ferrite and bainite lessen the hydrogen sensitivity of hot-sheared quenched 22MnB5 steels.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It is likely that the presence of ferrite may have contributed to a reduction of the HE susceptibility of MS-AHSS. Matsuno et al [53] observed the ability of ductile phases (e.g. ferrite and bainite) to reduce the hydrogen sensitivity of martensitic sheet steels.…”
Section: Martensitic Microstructurementioning
confidence: 99%
“…Therefore, hydrogen embrittlement has attracted much attention recently. [6][7][8][9][10][11][12][13][14][15][16] Matano et al 8) reported an evaluation of deformation microstructures and associated lattice defects in SUS 304 and SUS 316 L steels by positron lifetime measurements detecting vacancy-type defects created during tensile straining. Nagao et al 10) investigated the mechanism of fracture surface morphology changes at intergranular and quasi-cleavage in a hydrogen embrittled lath martensitic steel.…”
Section: Introductionmentioning
confidence: 99%
“…1,2) To ensure reliability and safety in the practical use of high strength steels, a reduction in the susceptibility to hydrogen embrittlement has become an important issue and hydrogen embrittlement has attracted much attention recently. [3][4][5][6][7][8][9][10][11][12][13] Koyama et al investigated the effect of hydrogen embrittlement of a Fe-18Mn-0.6C austenitic steel (wt.%) by tensile tests with hydrogen charging at various current densities. They reported that the work hardening behavior was not affected by the hydrogen charging.…”
Section: Introductionmentioning
confidence: 99%